Inteligentni transportni sistemi pri načrtovanju in usklajevanju gibanja in parkiranja letal na ploščadi letališča - Pavlin, Stanislav (Strojniški vestnik, 2004)
Airport aprons are areas for aircraft handling, parking and maintenance. According to international rules the number of positions at the apron has to be at least equal to the number of aircraft staying at any one time at the airport. The air traffic at Split Airport increased rapidly in the mid-90s when it became the UN logistics base for Bosnia and Herzegovina. There were nomeans nor free space for further expansion of the apron, so the traffic had to be reorganised and re-coordinated. Alternative positions and restrictions were introduced. A computer program for apron aircraft-traffic planning and coordination was developed, and then later upgraded in GIS (Geographic Information System) by the systems Arc View and Arc View Tracking Analyst. The basic function of the system is to suggest optimal aircraft movements and parking positions based on the planned and actual traffic, meeting aircraft safety spacing both in movement and in standing positions.
Keywords: gibanje letal; parkiranje letal; načrtovanje; koordinacija; letalski promet; parkiranje; nadzor